Human capital neurodiversity: an examination of stereotype threat anticipation - Priscott, Tamsin; Allen, Robby A. (Emerald, 2021)
Purpose The purpose of the study was to test the assumption of similarities between neurodivergents and other minority groups regarding their reaction to stereotype threat. In addition, it aimed to identify the source of stereotype threat and the neurodivergent's response to it. Design/methodology/approach Two studies were conducted. Study 1 employed three exercises consisting of brochures, learning sets and posters to test organisational cues, notions of intelligence and situational cues. It collected data from 53 participants to establish whether stereotype threat observed in visible difference such as race, gender and intelligence is equally relevant to neurodiversity. Study 2 consisted of interviews with 44 participants to establish stereotype threat source, reaction and effect on declaration of invisible difference. Findings Neurodivergents, defined by their invisible difference, react similarly to those with a visible difference with respect to organisational cues and stereotype threat. They will cognisantly define their behaviours depending upon those cues and stereotype threat. In doing so, they draw upon previous personal and work experiences. After the event, they will make a comparison to their assessment. If it is similar to their assessment, it reinforces it; however, if it is dissimilar, the neurodivergent will make an adjustment to the assessment. In both cases, the experience will form part of a future threat assessment. Research limitations/implications The research is limited by its interpretivist nature and sample comprising personnel within a UK government organisation. Practical implications The research has practical implications for employers, providing managers with a model to understand the impact a neurodivergents' previous experiences can have on their ability to interact within the workplace. Such understanding can provide insight into how best to utilise human capital. Originality/value This study makes a contribution to theory by expanding knowledge of neurodiversity in the workplace and by identifying the neurodivergents' reaction to the anticipation of a stereotype threat. In addition, it offers the stereotype threat anticipation conceptual model as a representation of the cognitive decisions made by neurodivergents to conceal or reveal their invisible difference.
Keywords: Diversity; Inclusion; Stereotypes; Neurodiversity